Biografia de um livro raro: manuscrito jesuítico na Biblioteca de Oswaldo Cruz - Silva, Marcelo de Lima da (2016)
The objective of this study is a rare book which is part of the rare book collection of the Fundação Oswaldo Cruz. The book, entitled Formulário Médico, was written in 1703 by Jesuits. It is a manuscript, composed of 225 pages, that describes medical prescriptions for the cure of various diseases through the use of flora and fauna found in locations where the Jesuits had missions. In addition to tracing the biography of this book, investigating its trajectory in the Fiocruz collection, our research examined how Formulário Médico was handled in the collection during decades. By dealing with this aspect, we hope to make significant contributions to the realization of the importance and responsibility of institutions which have collections such as this one regarding the appropriate manner of preserving works like this manuscript for the future.